Management Drink Alcohol in Supermarket in Denpasar City From the Department of Industry and Trade - Ni Putu Satya Wiryani; Desak Made Febri Purnama sari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this research is to analyze the management of alcoholic beverages in supermarkets in Denpasar City, focusing on regulation, supervision, and social and health impacts. The research method employed is a qualitative approach using in-depth interviews and observations with business actors, government officials, and the public. The findings reveal that although regulations on the sale of alcoholic beverages are in place, their implementation faces various challenges, particularly in terms of supervision and law enforcement. Many supermarket have note completely complied with the regulations, and public awareness of the dangers of alcohol remains low. In conclusion, there is a need for stronger regulations, enhanced supervision, and more intensive public education to create a safe and healthy environment regarding alcohol consumption in Denpasar.